DIGITAL TRANSFORMATION OF MANADO'S CULINARY MSMES: MARKETING ADAPTATION AND CREATIVE LOCAL PRODUCT INNOVATION - Priskila Walangitan; Rillie Sagai; Ferdy Rumambi; Tri Korengkeng; Ferlina Tandaju (SOSIOEDUKASI, 2025)
This study analyzes the mechanism of digital transformation of culture-based culinary MSMEs in Manado through a mixed methods approach with an explanatory sequential design. A total of 100 MSMEs under the guidance of the Manado IKM Center were respondents in the quantitative analysis using PLS-SEM, which showed that Digital Marketing Strategy and Digital Marketing Performance are the main determinants of business sustainability. Technology acceptance and cultural product characteristics have a significant effect on digital marketing strategy, while Digital Readiness and Cultural Creativity Process do not show a direct effect. Qualitative analysis using NVivo reinforced these findings by revealing the strategic role of training, mentoring, and cultural narratives in shaping digital capabilities. Overall, this study confirms that the success of MSME digital transformation is the result of synergy between internal capabilities, cultural values, and institutional support from the Manado IKM Center, which together facilitate the strengthening of digital marketing performance and business sustainability.